Mentoring and schooling decisions: Causal evidence - Armin Falk; Fabian Kosse; Pia Rosina Dovern-Pinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
Inequality of opportunity strikes when two children with the same academic performance are sent to diff erent quality schools because their parents di ffer in socio-economic status. Based on a novel dataset for Germany, we demonstrate that children are signi ficantly less likely to enter the academic track if they come from low socio-economic status (SES) families, even after conditioning on prior measures of school performance. We then provide causal evidence that a low-intensity mentoring program can improve long-run education outcomes of low SES children and reduce inequality of opportunity. Low SES children, who were randomly assigned to a mentor for one year are 20 percent more likely to enter a high track program. The mentoring relationship aff ects both parents and children and has positive long-term implications for children's educational trajectories.
Keywords: C90; I24; J24; J62; 330; mentoring; childhood intervention programs; education; human capital investments; inequality of opportunity; socio-economic status